IMPLEMENTASI HYBRID CONTRACK DI PEGADAIAN SYARIAH CPS PASAR LEGI JOMBANG - Muthammimatus Sa’idah; Arivatu Ni’mati Rahmatika (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2020)
In arum Tasjily, there are two intertwined contracts namely Rahn and Ijarah. Rahncontrack is a guarantee / guarantee that can be executed if the diligent crow fulfill his obligations. Whereas the ijarah agreement is the transfer of use rights over goods or services through payment of rental wages {‘ujrah} witout being fllowed by the transfer of ownership of the goods, there are several DSN-MUI fatwas governing the operation of the two contracts, one of which is the DSN-MUI Fatwa No :68 / DSN-MUI / III2008 concerning RahnTasjily. There is a compatibility between the DSN-MUI Fatwa governing the applicable provisions. This is used by the Pegadaian Syaiah Jombang Branch as a reference in policy making. In this study the authors used a descriptive quantitative apporoach, with data and some understanding of the source of the problem.